Acetabular reaming and sartorius muscle pedicle iliac bone grafting in the treatment of developmental dysplasia of the hip in older children: a retrospective study of 15 patients with more than two years follow-up. (2020) - Fan, Zhang; Cong, Luo; Hang, Liu; Ming, Li; Jun, Wu; Zujie, Hu; Haoyu, Li
Abstract: Purpose: Despite the early diagnosis and treatment of developmental dysplasia of the hip (DDH), some older children still need open reduction. It is usually difficult to get a satisfactory reduction particularly in patients with acetabular defect. The purpose of this study was to evaluate the short-term outcomes of acetabulum reaming and sartorius muscle pedicle iliac bone grafting in the treatment of older children with DDH and acetabular defect. Methods: The records of 15 patients with DDH (mean age 113.9 months (sd 29); 17 hips) who were treated with the reported technique between February 2015 and January 2017 were retrospectively reviewed. All patients acquired regular clinical and radiographic follow-ups, and alterations in the acetabular index, centre-edge angle and acetabular head index were measured. Joint function and radiographic results were evaluated with McKay and Severin modified criteria, respectively. Results: A total of 15 patients were followed up for mean 32.4 months (sd 6.9). The percentages of excellent and good conditions were 94.1% (16/17) according to the Severin modified criteria and 88.2% (15/17) according to the McKay modified criteria. Avascular necrosis of the femoral head and redislocation only occurred in one hip. No cases of ankylosis or bone graft absorption occurred during the follow-up. Conclusion: Reaming the acetabulum and sartorius muscle pedicle iliac bone grafting for repairing the acetabular defect can recover the arcuate structure by increasing the volume of the acetabulum, which is beneficial for achieving a concentric reduction. The short-term outcome was satisfactory, while the long-term results need to be further observed. Level of Evidence: IV – retrospective study